Openings and resistances: Women in the Bangladesh Civil Service - Sultan, Maheen; Jahan, Ferdous (Routledge, 2022)
This book chapter was published in the book named Public Policy and Governance in Bangladesh Forty Years of Experience and the definite version is available at : https://www.taylorfrancis.com/chapters/edit/10.4324/9781315621043-24/openings-resistances-women-bangladesh-civil-service-maheen-sultan-ferdous-jahan